A practical guide to pharmaceutical analyses using X-ray powder diffraction. Issue 2 (June 2019) - Fawcett, T. G.; Gates-Rector, S.; Gindhart, A. M.; Rost, M.; Kabekkodu, S. N.; Blanton, J. R.; Blanton, T. N.
Abstract : Advances in instrumentation, software applications, and database content have all contributed to improvements in pharmaceutical analyses by powder diffraction methods in the 21 st century. When compared to the globally harmonized United States Pharmacopeia General Chapter <941>, "Characterization of Crystalline and Partially Crystalline Solids by X-ray Powder Diffraction", many historic problems in pharmaceutical analysis have been addressed by combinations of improved methods and instrumentation. Major changes in the last 20 years include (i) a dramatic lowering in detection capability and detection limits, (ii) enhanced capabilities for dynamic measurements such as in situ analyses under a variety of conditions, and (iii) the ability to identify and characterize nanomaterials, non-crystalline, and amorphous materials by both coherent and incoherent scattering profiles.